Clinical and pathological analysis in 258 childhood patients with primary IgA nephropathy - XIE min; FENG Shi-pin; LUO Wei; WANG Li; DUAN Qin-wei; LIU Xi; LIU Jun (Linchuang shenzangbing zazhi)
Objective To analyze the clinical and pathological characteristics in 258 childhood patients with IgA nephropathy.Methods Analysis was performed by using the clinical and pathological data of 258 children with IgA nephropathy who were in Chengdu Women and Children’s Central Hospital from 1stDec 2008 to 1st Dec 2017. All renal biopsies were examined by light microscopy, immunofluorescence, and electron microscopy. Correlations between Clinical features and pathological grades were investigated.Results IgA nephropathy was diagnosed in 258 cases with a mean age（9.3±3.2） years and a male to female ratio of 2.23∶1.84 cases with isolated hematuria were pathologic grade II（51.1%）. 45 cases with isolated proteinuria were pathologic grade II（40%）.72 cases with hematuria and proteinuria were pathologic grade III（56.9%）. 4 cases with acute nephritis, 2 cases were pathologic grade III,1 case was pathologic gradeII and1 was pathologic gradeⅣ, respectively.50 cases with nephrotic syndrome were pathological grade III（80%）.3 cases of chronic nephritis,2 were pathologic grade Ⅳ,1 was pathologic grade V. Among all the cases, pathologic grade II and grade III were in majority with proportion 34.5% and 38.4 %. The main types of immune complex deposits were IgA+IgM+C3 and IgA+C3. The proportion of IgA, IgM, and C3 co-deposition was significantly higher in cases of nephrotic syndrome than isolated hematuria（P<0.05）. Conclusions Different clinical phenotypes have different pathologic renal lesions, clinical manifestations showed relations with pathological to some extent. In the patients who showed acute nephritis, nephrotic syndrome, and chronic nephritis,the damage were more serious and worse. We can predict the risk of progression of IgA nephropathy based on the combination of the clinical grade and the histological grade.